Does social capital attributes effect the employability readiness among engineering graduates of the higher education institutes in Oman / Masoud Rashid Al Hinai, Abul Bashar Bhuiyan and Nor Azilah Husin - Rashid Al Hinai, Masoud; Bhuiyan, Abul Bashar; Husin, Nor Azilah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The aim of this study is to investigate the effects of Social Capital attributes on the employability readiness of the engineering graduates of the Higher Education Institutes in Oman. The study adopted a self-directed structured questionnaire that was distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used the structural equation modelling (SEM) to analyse the collected data. The findings of the statistical analysis of the study showed the significant contribution of social activities in the attainment of team-work, communication, proficiency of the English language, and problem-solving skills. As a result, the involvement of the graduates in social activities strongly influences the awareness of career information which in return affects positively the graduates ’ readiness for employability. Specifically, study findings showed that the social capital attributes factor has a high influence on the Readiness for Employability of the graduates in Oman. Finally, the study’s implementations and recommendations could be transferred to the Gulf and Arab or other countries’ contexts that have similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.